Effect of Sauropus androgynus Leaf Extract and Fish Oil Plus Vitamin E on Performance, Carcass Quality, and Meat Amino Acid Composition in Broiler Chickens - Urip Santoso; Yosi Fenita; Kususiyah Kususiyah (Agricultural Faculty, 2021)
ABSTRACT. This study aimed to evaluate the effect of Sauropus androgynus leaf extract (SALE), lemuru fish oil and vitamin E supplementation on performance, carcass quality, and amino acid composition of broiler meat. One hundred and ninety-five broilers aged 21 days were distributed into 13 groups as follows: broilers were fed diet with 0.5% commercial supplement feed (P0), 10 g/kg SALE plus 1% lemuru fish oil (LFO) (P1), 10 g SALE/kg and LFO 1% plus 60 mg vitamin E (P2), 10 g SALE/kg and LFO 2% (P3), 10 g SALE/kg and LFO 2% plus 60 mg vitamin E (P4), 10 g SALE/kg and LFO 3% (P5), 10 g SALE/kg and LFO 3% plus 60 mg vitamin E (P6), 18 g SALE/kg and LFO 1% (P7), 18 SALE g/kg and LFO 1 % plus 60 mg vitamin E (P8), 18 g SALE/kg and FLO 2% (P9), 18 SALE g/kg and FLO 2% plus vitamin E (P10), 18 g SALE/kg and LFO 3% (P11 ), and 18 g SALE/kg and LFO 3% plus 60 mg vitamin E. The variables measured were performance, carcass quality, organoleptic properties, protein and amino acid composition of meats. The experimental results showed that the treatment had no significant effect (P 0.05) on body weight, feed consumption, feed conversion ratio, carcass weight, meat color, meat odor, meat taste, and cooking losses. However, the treatment had a significant effect (P 0.05) on carcass color, spleen weight, and protein content. In addition, the treatment also changes the amino acid composition of the meat. In conclusion, supplementation of 18 g SALE/kg diet, 3% LFO plus vitamin E resulted in meat with the highest protein and amino acid content. (Pengaruh ekstrak daun katuk, minyak ikan plus vitamin E terhadap performa, kualitas karkas, dan komposisi asam amino pada broiler) ABSTRAK. Penelitian ini bertujuan untuk mengevaluasi pengaruh suplementasi ekstrak daun katuk (EDK), minyak ikan lemuru, dan vitamin E terhadap performa, kualitas karkas, dan komposisi asam amino daging broiler. Seratus sembilan puluh lima ekor broiler umur 21 hari didistribusikan ke dalam 13 kelompok sebagai berikut: broiler diberi pakan mengandung 0,5% pakan imbuhan komersial (P0), 10 g/kg EDK plus 1% minyak lemuru (MIL) (P1), EDK 10 g/kg dan MIL 1% plus 60 mg vitamin E (P2), EDK 10 g/kg dan MIL 2% (P3), EDK 10 g/kg dan MIL 2% plus 60 mg vitamin E (P4), EDK 10 g/kg dan MIL 3% (P5), EDK 10 g/kg dan MIL 3% plus 60 mg vitamin E (P6), EDK 18 g/kg dan MIL 1% (P7), EDK 18 g/kg dan MIL 1% plus 60 mg vitamin E (P8), EDK 18 g/kg dan MIL 2% (P9), EDK 18 g/kg dan MIL 2% plus vitamin E (P10), EDK 18 g/kg dan MIL 3% (P11), dan EDK 18 g/kg dan MIL 3% plus 60 mg vitamin E. Variabel yang diukur adalah performa, kualitas karkas, dan sifat organoleptik, protein dan komposisi asam amino daging. Hasil penelitian menunjukkan bahwa perlakuan berpengaruh tidak nyata (P0,05) terhadap berat badan, konsumsi pakan, konversi pakan, berat karkas, warna daging, bau daging, rasa daging, dan susut masak. Akan tetapi perlakuan berpengaruh nyata (P0,05) terhadap warna karkas, berat limfa, kadar protein. Selain itu, perlakuan juga mengubah komposisi asam amino daging. Kesimpulannya, suplementasi 18 g EDK/kg pakan, 3% MIL plus vitamin E menghasilkan daging dengan kandungan protein dan asam amino tertinggi.